(untitled) (Computer systems and information technologies, 2022)
Research into the reliability of computer systems is important at all stages of their life cycle. Such studies are conducted to ensure the required level of reliability in the development, to ensure the level of reliability during operation and to assess the reliable operation in the process of modernization of such systems. Reliability research is carried out on the basis of the indicators received in the course of modeling. The main reliability models that have found their practical use are considered in the paper: structural-logical schemes, fault trees and Markov processes, as well as the main indicators that characterize them are determined. Since the above calculation methods do not take into account the factors that affect the overall reliability of computer systems, namely the reliability of software and databases, the human factor, the paper propose an approach and method for evaluating a general reliability indicator of computer systems.